Pengembangan Sistem E-commerce untuk Promosi Digital pada Produk UMKM Menggunakan OpenCart di Kecamatan Panai Tengah - Alia, Rahma; Annas, Firdaus; Ariska, Vina; Wandira, Raju (Yayasan Lembaga Studi Makwa, 2023)
The promotion of MSME products in Panai Tengah District is still limited to the use of social media platforms such as Facebook and WhatsApp. Moreover, disorganized product management makes it difficult for customers to access information. This situation causes MSME flagship products to be less recognized in wider markets. Therefore, innovative solutions are needed to help MSMEs utilize digital technology more effectively. This study aims to develop a web-based e-commerce system using OpenCart to enhance the competitiveness of MSME products while addressing challenges in digital product management. The research method employed is research and development (R&D) with the 4D model (Define, Design, Develop, Disseminate). The resulting system is capable of organizing products digitally with a more structured, professional, and customer-friendly display. The findings indicate that the implementation of OpenCart improves product visibility, expands customer access, and significantly contributes to the competitiveness of MSMEs in the digital marketplace. Furthermore, this system helps MSMEs reach consumers in broader regions through integrated search and online marketing features. By utilizing web-based technology, MSMEs in Panai Tengah District can expand their market reach, enhance product appeal, and support local economic growth. This study concludes that digital technology like OpenCart plays a crucial role in the digital transformation of MSMEs, improving promotional strategies, and fostering the sustainability of MSMEs in the digital era.